(untitled) (Surya Abdimas, 2023)
Criminals or convicts placed in detention centers or prisons with the provisions of the law actually aim to provide a deterrent effect and provide religious understanding so that after the detention period is over they can behave better and not make the same mistakes. However, many of them, after leaving detention, no longer have the trust of the local community where they come from, so that it is difficult for these ex-convicts to get jobs and do not have the skills to become entrepreneurs. This is what makes ex-convicts lose confidence and even repeat the same mistakes. The method of delivering learning material uses a participatory learning approach by providing material and implementing practices. The implementation of this community service activity was carried out at the Bengkulu IIB Prison which was attended by 30 convicts. The Community Service Implementation Team has provided motivation and tips for success for prisoners, conducted cosmetology and beauty training based on the use of domestic production technology, and introduced other alternatives for sources of income such as the manufacture and marketing of organic masks intended for women. convicts as provisions in improving their health. skills at the Class IIB Correctional Institution of the Bengkulu Ministry of Law and Human Rights. Therefore, the service team hopes that from this service the prisoners will gain alternative skills in welcoming the prisoner’s free period later.